KEDUDUKAN QANUN DALAM PANDANGAN UNDANG-UNDANG NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Aidil Fan (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2019)
This research is focused on the issue of formulating the Qanun as an embodiment of the Authority of the Aceh Government, but there is supervision from the Central government. This research uses a descriptive analytical method, which is a study that provides an overview of the scope and review of the formulation of Qanun in Aceh that remains under the supervision of the Central Government. This study also uses the normative juridical method with the statutory approach. This research concludes that in the context of supervision, the Central Government can suspend or cancel a Qanun if it is considered to be in conflict with the higher laws. This preventive supervision is carried out on the policies of the Regional Government which regulates the regional budget of revenue and expenditure, local taxes and other regulations that can create a high cost economy.